Heart-rate variability recording time and performance in collegiate female rowers - Sherman, S. R.; Holmes, C. J.; Hornikel, B.; MacDonald, H. V.; Fedewa, M. V.; Esco, M. R. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To assess the agreement of the root mean square of successive R-R interval (RMSSD) values when recorded immediately upon waking to values recorded later in the morning prior to practice, and to determine the associations of the RMSSD recordings with performance outcomes in female rowers. Methods: A total of 31 National Collegiate Athletic Association Division I rowers were monitored for 6 consecutive days. Two seated RMSSD measurements were obtained on at least 3 mornings using a smartphone-based photoplethysmography application. Each 1-minute RMSSD measure was recorded following a 1-minute stabilization period. The first (T1) measurement occurred at the athlete`s home following waking, while the second (T2) transpired upon arrival at the team`s boathouse immediately before practice. From the measures, the RMSSD mean and coefficient of variation were calculated. Two objective performance assessments were conducted on an indoor rowing ergometer on separate days: 2000-m time trial and distance covered in 30 minutes. Interteam rank was determined by the coaches, based on subjective and objective performance markers. Results: The RMSSD mean (intraclass correlation coefficient = .82; 95% CI, .63 to .92) and RMSSD coefficient of variation (intraclass correlation coefficient = .75; 95% CI, .48 to .88) were strongly correlated at T1 and T2, P < .001. The RMSSD mean at T1 and T2 was moderately associated with athlete rank (r = -.55 and r = -.46, respectively), 30-minute distance (r = .40 and r = .41, respectively), and 2000 m at T1 (r = -.37), P < .05. No significant correlations were observed for the RMSSD coefficient of variation. Conclusion: Ultrashort RMSSD measurements taken immediately upon waking show very strong agreement with those taken later in the morning, at the practice facility. Future research should more thoroughly investigate the relationship between specific performance indices and the RMSSD mean and coefficient of variation for female collegiate rowers.Herzfrequenzvariabilität bei der Aufzeichnung von Zeit und Leistung bei Collegerudererinnen